Noninvasive release of tendons using MRI guided focused ultrasound: a hybrid therapy using long-pulse focused ultrasound followed by thermal ablation - William Chu Kwan; Imogen den Otter-Moore; Ari Partanen; Karolina Piorkowska; Unni Narayanan; Adam C. Waspe; James M. Drake (International Journal of Hyperthermia)
Introduction Magnetic Resonance-guided Focused Ultrasound (MRgFUS) thermal ablation is an effective noninvasive ultrasonic therapy to disrupt in vivo porcine tendon but is prone to inducing skin burns. We evaluated the safety profile of a novel hybrid protocol that minimizes thermal spread by combining long-pulse focused ultrasound followed by thermal ablation.Methods In-vivo Achilles tendons (hybrid N = 15, thermal ablation alone N = 21) from 15 to 20 kg Yorkshire pigs were randomly assigned to 6 treatment groups in two studies. The first (N = 21) was ablation (600, 900, or 1200 J). The second (N = 15) was hybrid: pulsed FUS (13.5 MPa peak negative pressure) followed by ablation (600, 900, or 1200 J). Measurements of ankle range of motion, tendon temperature, thermal dose (240 CEM43), and assessment of skin burn were performed in both groups.Results Rupture was comparable between the two protocols: 1/5 (20%), 5/5 (100%) and 5/5 (100%) for hybrid protocol, compared to 2/7 (29%), 6/7 (86%) and 7/7 (100%) for the ablation-only protocol with energies of 600, 900, and 1200 J, respectively. The hybrid protocol produced lower maximum temperatures, smaller areas of thermal dose, fewer thermal injuries to the skin, and fewer full-thickness skin burns. The standard deviation for the area of thermal injury was also smaller for the hybrid protocol, suggesting greater predictability.Conclusion This study demonstrated a hybrid MRgFUS protocol combining long-pulse FUS followed by thermal ablation to be noninferior and safer than an ablation-only protocol for extracorporeal in-vivo tendon rupture for future clinical application for noninvasive release of contracted tendon.